Improving Compliance with a Rounding Checklist through Low- and High-technology Interventions: A Quality Improvement Initiative. Issue 4 (July 2021) - Carr, Leah H.; Padula, Michael; Chuo, John; Cunningham, Megan; Flibotte, John; O'Connor, Theresa; Thomas, Beth; Nawab, Ursula
Abstract : Introduction: Checklists aid in ensuring consistency and completeness in medical care delivery. However, using an improvement and safety checklist during rounds was variable in our neonatology intensive care unit (NICU), and completion was not tracked sustainably. This quality improvement (QI) initiative's primary aim was to increase compliance with checklist completion from 31% to >75% within 1 year. Methods: A multidisciplinary QI team identified barriers to checklist completion and implemented a human factors-focused low-technology intervention (redesign of a hard-copy checklist) and later a high-technology clinical decision support tool within the electronic health record. The primary outcome measure was percent compliance with the use of the checklist. Process metrics included the duration of checklist completion. Balancing measures included staff perceptions of work burden and question relevance. Results: Major barriers to checklist utilization were inability to remember, rounding interruptions, and perceived lack of question relevance to patients. Average biweekly checklist compliance improved from 31% before interventions to 80% after interventions. Average checklist completion time decreased from 46 to 11 seconds. Follow-up surveys demonstrated more respondents found questions "completely relevant" (34% pre versus 43% post) but perceived increased work burden (26% pre versus 31% post). Conclusions: Using QI methodology, human factors-based interventions, and a novel clinical decision support tool, we significantly improved efficiency and checklist compliance and created an automated, sustainable method for monitoring completion and responses. This foundational project provides an infrastructure broadly applicable to QI work in other healthcare settings.